Geluidsband t.g.v. de opening van het Verzetsmuseum in de tijdelijke behuizing in de Nieuwe Batavierenstraat
Geluidsband t.g.v. de opening van het Verzetsmuseum in de tijdelijke behuizing in de Nieuwe Batavierenstraat.